A boy with bilateral SUNA: A case report. (September 2017) - Vuković Cvetković, Vlasta; Jensen, Rigmor Højland
Background: Short-lasting unilateral neuralgiform headache attacks (SUNA) is a primary headache characterized by frequent attacks of severe headaches in association with ipsilateral cranial autonomic features. SUNA is defined as a strictly unilateral pain and bilateral cases are very unusual, so secondary causes should be searched for vigorously if there are bilateral symptoms. Despite a number of therapeutic trials, effective management for the majority of SUNA patients is not available at present. Management of SUNA is often difficult. Case: We report the case of a young boy with bilateral SUNA attacks, with no detected underlying cause, who is responsive to indomethacin. Conclusion: Rarely, primary SUNA can present with bilateral symptoms. According to our experience in this case, indomethacin should always be offered to patients with suspected SUNA.